In vitro evaluation of the schistosomicidal effect of the extracts, fractions and major 3-hydroxy-2,6-dialkyl-substituted piperidine alkaloids from the flowers of Senna spectabilis (Fabaceae) - Castro, Andreisa Teixeira de; Castro, Aline Pereira; Silva, Matheus Siqueira; Monteiro de Souza, Isabella Maria; Martins-Souza, Raquel Lopes; Chagas-Paula, Daniela Aparecida; Leomil Coelho, Luiz Felipe; Bolzani, Vanderlan da Silva [UNESP]; Pivatto, Marcos; Viegas Junior, Claudio; Marques, Marcos Jose (Elsevier B.V., 2016)
In this work, we present the in vitro schistosomicidal activity evaluation of the most active dichloromethane fraction (FDm) (ED50 = 83.5 mu g/mL) and of a mixture of the major alkaloids ((-)-cassine/(-)-spectaline, C/E) (ED50 = 37.4 mu g/mL) from the flowers of Senna spectabilis against adult worms and cercariae. We also demonstrate other toxic effects including paralysis of the adult worms, inhibition of the secretory activity, tegument lesions and cercaricidal activity. In the association test of Praziquantel (PZQ)-C/E, we observed up to 80% mortality of Schistosoma mansoni in comparison to PZQ monotherapy. Due to the diversity of the toxic effects, the schistosomicidal activity of C/E is likely a result of a multitarget mechanism involving the tegument, secretory system and neuromotor action. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Schistosomiasis; Senna spectabilis; Alkaloids; Fluorescent probes